Vegetation structure and relative humidity drive the diurnal foraging activity of Malaysian giant ant workers in urban fragmented forests - Md Sharif, Badrul Azhar; Razi, Norhisham; Sanusi, Ruzana; Lechner, Alex; Ashraf, Mohamad; Wan Zaki, Wan Mamat; Jafni, Farhan (John Wiley and Sons, 2024)
The impacts of urban forest fragmentation on tropical ant foraging activity are poorly understood. The Malaysian giant ant (Dinomyrmex gigas) is among the largest ant species worldwide. Colonies of this species contribute to important ecosystem processes such as predation and nutrient cycling in the tropical forests of Southeast Asia. Here, we compared the diurnal foraging activity of D. gigas workers in urban-fragmented and contiguous forests, and investigated how this was shaped by key environmental factors such as vegetation structure and microclimate. Specifically, we sampled ground-foraging D. gigas workers in four urban/semi-urban forest patches and two contiguous forests in Peninsular Malaysia across the wet and dry seasons. Surprisingly, we found that some urban forest patches, irrespective of area, supported greater foraging activity of D. gigas workers than contiguous forests. These differences in foraging activity were explained by differences in multiple stand-level variables between urban forests patches and contiguous forests. Specifically, the abundance of foraging D. gigas workers increased with number of trees with Diamater at breast height (DBH) 5–30 cm, but it decreased with relative humidity, canopy cover, number of palms, number of shrubs and trees with DBH <5 cm. Our study highlights the importance of urban forest patches, microclimate and vegetation structure for driving the diurnal foraging activity of Malaysian giant ant. Small and relatively large forest patches were of comparable importance for the maintenance of biodiversity in urban landscapes. In the absence of landscape connectivity, reforestation is the most feasible option to restore the natural habitat of D. gigas in urban forest patches and mitigate microclimatic edge effects.